Associations of depression, anxiety and antidepressants with histological severity of nonalcoholic fatty liver disease. (7th April 2013) - Youssef, Nagy A.; Abdelmalek, Manal F.; Binks, Martin; Guy, Cynthia D.; Omenetti, Alessia; Smith, Alastair D.; Diehl, Anna Mae E.; Suzuki, Ayako
Abstract Background Depression and anxiety are common in patients with nonalcoholic fatty liver disease (NAFLD). However, their associations with histological severity of NAFLD are unknown. Aim This study examined the association(s) of depression, anxiety and antidepressant pharmacotherapy with severity of histological features in patients with NAFLD. Methods We analysed 567 patients with biopsy‐proven NAFLD enrolled in the Duke NAFLD Clinical Database. Depressive and anxiety symptoms were assessed using the Hospital Anxiety & Depression Scale (HADS). The associations of depression and anxiety with severity of histological features of NAFLD were analysed using multiple logistic (or ordinal logistic) regression models with and without adjusting for confounding factors. Result Subclinical and clinical depression was noted in 53% and 14% of patients respectively. Subclinical and clinical anxiety was noted in 45% and 25% of patients respectively. After adjusting for confounders, depression was significantly associated with more severe hepatocyte ballooning in a dose‐dependent manner (likelihood ratio test, P = 0.0201); adjusted cumulative odds ratio (COR) of subclinical and clinical depression for having a higher grade of hepatocyte ballooning were 2.1 [95% CI, 1.0, 4.4] and 3.6 [95% CI, 1.4, 8.8]. Conclusions In patients with NAFLD, depression was associated with more severe hepatocyte ballooning. Further investigation exploring pathobiological mechanisms underlying the observed associations and potential effects of antidepressant pharmacotherapy on NAFLD liver histology is warranted.